ECONOMIC FEATURES OF PUBLIC-PRIVATE PARTNERSHIP DEVELOPMENT: GLOBAL TRENDS AND DOMESTIC EXPERIENCE OF THE PRE-WAR PERIOD - Kwilinski, Aleksy; Maslov, Vladyslav; Luzhna, Anastasiia (Socio-economic relations in the digital society, 2022)
In the conditions of globalization, the development of the knowledge economy, and the digitalization of all spheres of activity, the most effective form of cooperation between the state and business entities - business and private individuals in the field of education and science, and the way of financing educational and scientific projects is the public-private partnership (PPP). The development and implementation of effective mechanisms for the interaction of the state, science, and business on the basis of PPP, which would correspond to modern conditions, the search for effective forms and tools for financing PPP projects is an urgent task today. The analysis carried out in the article made it possible to single out 5 main trends in the development of PPPs (quantitative growth of PPPs in the world and in the EU; diversification of the PPP market by countries and sectors of the economy; infrastructural orientation of PPPs; state support of a certain type of PPPs either in a certain industry or in a certain direction; development PPP in the innovative sphere), which made it possible to reach a conclusion in the process of generalization about the areas in which PPP was concentrated in Ukraine. On the basis of the statistical data, the article identifies the main areas of concentration of PPP projects in Ukraine in the pre-war period. Considering the multi-component nature of PPP goals, the scientific work summarizes and details the scenarios of the activation of PPP relations in Ukraine (budgetary and financial, resource, innovation, and investment).